Application of the 2(5H)furanone motif in the synthesis of new thiopyrano[2, 3-d]thiazoles via the hetero-Diels–Alder reaction and related tandem processes. Issue 30 (27th July 2016) - Lozynskyi, Andrii; Zimenkovsky, Borys; Karkhut, Andriy; Polovkovych, Svyatoslav; Gzella, Andrzej K.; Lesyk, Roman
Graphical abstract: Highlights: 2(5 H )Furanone was used for the synthesis of thiopyrano[2, 3- d ]thiazoles. Acylation–hetero-Diels–Alder reaction was used for the synthesis of chromenothiopyranothiazoles. Regio- and stereoselectivities of the reactions were discussed. Abstract: Novel thiopyrano[2, 3- d ]thiazole derivatives were synthesized from 5-arylidene-4-thioxo-2-thiazolidinones and 2(5 H )furanone in 62–79% yields via hetero-Diels–Alder reactions and related acylation-based tandem processes. The reaction of 5-(4-fluorophenyl)-4-thioxo-2-thiazolidinone with 2(5 H )furanone was studied by DFT at the M06-2X/6-31+G(d, p) level. The stereo- and regioselectivities of cycloaddition were confirmed by NMR spectra and single-crystal X-ray diffraction analyses.